Historical Learning Behavior of High School Students During the Covid-19 Pandemic - Teguh, Muhammad; Basri, Wahidul (Yayasan Sembilan Pemuda Indonesia, 2021)
This article was written with the aim of analyzing the behavior of high school students and all of their factors during history learning during the Covid-19 pandemic, so that knowing the history learning behavior of high school students and responses from high school teachers related to student behavior in the history learning process during the Covid-19 pandemic and analyzing how the reinforcement measures carried out by high school teachers towards students and the effect felt during online learning. The research method used was descriptive qualitative. The subjects of the study were research articles related to students' historical learning behavior during the Covid-19 pandemic, The sample of research articles is 26 journals consisting of national journals and international journals. The results of this study were 1) forms of student behavior in various history lessons; 2) student behavior is influenced by the creativity ability of teachers and the role of the family, and 3) The history teacher provides reinforcement during the online history learning process to students. The conclusion of this study is to maximize the history learning behavior of high school students during the pandemic has 5 (five) aspects learning and management of teaching in the Covid-19 era, know the benefits of learning history using Google classroom, increasing the effectiveness of the teaching and learning process during the Covid-19 Pandemic, the role of families in accompanying student, and increase student activeness in taking online learning.